Investigating the impact of climate change on the tourism sector: evidence from a sample of island economies. Issue 2 (8th April 2019) - Seetanah, Boopen; Fauzel, Sheereen
Abstract : Purpose: Although it is a widely accepted fact that climate change can negatively impact on tourism demand and affect the economies at the socio-economic level, empirical studies on the climate change tourism development nexus has been quite scant, especially for the case of island economies that are heavily dependent on tourism. This study aims to supplement the literature on climate change and tourism by empirically assessing the relationship between climate change and tourist arrivals for the case of 18 small island developing states over the period from 1989 to 2016. Design/methodology/approach: This paper uses dynamic panel data techniques, namely, a panel vector autoregressive framework, which accounts for dynamic and endogeneity issues. Findings: The results from the analysis confirm the existence of a significant relationship between climate change and tourism demand in both the long-run and short run. Further analysis shows a bi-directional causality between climatic change and tourism demand while the study also confirms the tourism led growth hypothesis. Research limitations/implications: This research supplements the literature on the tourism-environment link, especially for tourism dependent island economies. Practical implications: Results from this study are important to policymakers who should spare no effort to mitigate the effect of adverse climatic change in the context of tourism development. Originality/value: This study is built on a unique data set for a sample of island economies and interestingly adopts dynamic panel data analysis to account for dynamics and endogenity in the climate change-tourism development nexus.